OBSERVATIONS ON SOME ASPECTS OF SPOILAGE IN FRESH AND FROZEN PRAWNS - Pillai, V Krishna; Shsstri, P V K; Nayar, M R (Indian Journal of Fisheries, 2011)
THE prawn freezing factories in Cochin receive their supplies of raw materials from all over the West Coast. Some factories have separate peehng centres in most of these places and the prawns collected from nearby fishing villages are peeled and deveined or beheaded and deveined as the case may be, cleaned and packed in ice at these centres before transporting to the factories. It often happens that the material thus transported takes more than 24 hoxirs to reach the factories. Icing of the material at the peeUng site helps in preventing bacterial spoilage during the long period of transport. But the success of icing will largely depend on the amount of ice used and how it is applied. If the requisite quantity of ice is not used the material will not only be not cooled to the desired level but its temperature will rise up during the long trip to the factory creating favourable conditions for normal spoilage processes to continue.